Investigating process parameters to enhance (hemi)cellulolytic enzymes activity produced by Trichoderma reesei RUT-C30 using deoiled oil palm mesocarp fiber in solid-state fermentation - Al-Qassab, Ali Abdulkareem; Zakaria, Mohd Rafein; Yunus, Robiah; Salleh, Mohamad Amran Mohd; Mokhtar, Mohd Noriznan (Elsevier, 2024)
This study investigates the synthesis of (hemi)cellulolytic enzymes, including endoglucanase (CMCase), xylanase, and β-glucosidase, employing Trichoderma reesei RUT-C30 and deoiled oil palm mesocarp fiber (OPMF) through solid-state fermentation (SSF). The objective was to determine the optimal process conditions for achieving high enzyme activities through a one-factor-at-a-time approach. The study primarily focused on the impact of the solid-to-liquid ratio, incubation period, initial pH, and temperature on enzyme activity. The effects of OPMF pretreatment, particularly deoiling and fortification, were explored. This approach significantly improved enzyme activity levels compared to the initial conditions, with CMCase increasing by 111.6 %, xylanase by 665.2 %, and β-Glucosidase by 1678.1 %. Xylanase and β-glucosidase activities, peaking at 1346.75 and 9.89 IU per gram dry substrate (GDS), respectively, under optimized conditions (1:4 ratio, pH 7.5, 20 °C, 9-day incubation). With lower moisture levels, CMCase reached its maximum activity of 227.84 IU/GDS. The study highlights how important it is for agro-industrial byproducts to support environmentally sustainable practices in the palm oil industry. It also emphasizes how differently each enzyme reacts to changes in process parameters.